Catalytic Asymmetric [4 + 2] Additions with Aliphatic Nitroalkenes - Bartelson, Keith J. (2011)
We describe an unprecedented cycloaddition reaction of 2-pyrones with aliphatic nitroalkenes catalyzed by a new bifunctional cinchona alkaloid-derived catalyst bearing a bulky TIPS-ether at the 9-position. The [2.2.2] bicyclic adducts were obtained in good yield with excellent diastereo- and enantioselectivity. Carbon isotope effects were measured by (13)C NMR and are indicative of a stepwise mechanism. Finally, a synthetic application is demonstrated, highlighting the utility of the cycloadducts.